2006
DOI: 10.1002/chin.200627017
|View full text |Cite
|
Sign up to set email alerts
|

7Li NMR and Two‐Dimensional Exchange Study of Lithium Dynamics in Monoclinic Li3V2(PO4)3.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(60 citation statements)
references
References 2 publications
1
59
0
Order By: Relevance
“…The first 7 Li MAS NMR study of LiVPO4F was reported by Goward et al 10 but they did not provide any explanation of these additional signatures. Kosova et al 11 suggested more recently that these extra signals would correspond to the three Li sites of the anti-Nasicon Li3V2(PO4)3, which could be present as impurity, even though their positions do not match exactly those reported in other studies 3,12 . In fact, recently 13 , using 2D 7 Li NMR experiments, we could show that the additional signals correspond to Li sites close to structural and/or chemical defects in LiVPO4F, and not to Li in impurity phases as suggested previously 11 .…”
Section: Introductionmentioning
confidence: 88%
“…The first 7 Li MAS NMR study of LiVPO4F was reported by Goward et al 10 but they did not provide any explanation of these additional signatures. Kosova et al 11 suggested more recently that these extra signals would correspond to the three Li sites of the anti-Nasicon Li3V2(PO4)3, which could be present as impurity, even though their positions do not match exactly those reported in other studies 3,12 . In fact, recently 13 , using 2D 7 Li NMR experiments, we could show that the additional signals correspond to Li sites close to structural and/or chemical defects in LiVPO4F, and not to Li in impurity phases as suggested previously 11 .…”
Section: Introductionmentioning
confidence: 88%
“…Two‐Dimensional Exchange Spectroscopy (2D EXSY) has become one of the most common NMR methods for studying chemical exchange in the slow motion regime. This experiment has been used to study of lithium ion dynamics in a number of Li transition metal oxide and phosphate analogs for energy storage applications, including oxides (LiMn 2 O 4 ), nitrides (Li 7 MnN 4 ), and phosphates (Li 3 M 2 (PO 4 ) 3 , M=V or Fe) Exchange is observed experimentally in the form of off‐diagonal “cross peaks” in the 2D spectrum (see Figure ), where the intensity of the cross peak relative to the diagonal peak intensity is the sum of chemical and spin exchange between two nuclei. Under fast MAS conditions (>40 kHz), spin exchange is not likely to be observed for 6 Li or 7 Li due to the tendency of the MAS to average any spin diffusion effects resulting from homonuclear dipolar coupling between small γ 7 Li and 6 Li nuclei.…”
Section: Nmr Methods For Studying Chemical Exchange In Battery Materialsmentioning
confidence: 99%
“…Two‐dimensional exchange spectra of Li 3 V 2 (PO 4 ) 3 at room temperature with mixing times of A, 0 ms and B, 0.5 ms. Adapted with permission from Cahill et al …”
Section: Nmr Methods For Studying Chemical Exchange In Battery Materialsmentioning
confidence: 99%
“…Chemical exchange rate constant between Li metal and the SEI (kex), SEI population (Pa), fraction of the SEI which undergoes exchange (f), and fraction of the Li metal which undergoes exchange (g) based on Bloch-McConnell fits of variable temperature data shown in Figure S17 for 0.5 M LiTFSI at 253 K, 293 K, and 333 K. Table S3. Chemical exchange rate constant between Li metal and the SEI (kex), SEI population (PSEI), fraction of the SEI which undergoes exchange (fSEI), and fraction of the Li metal which undergoes exchange (fmetal) for exchange between Li metal and the SEI (1), as well as the SEI and the electrolyte (2). The values shown are extracted from Bloch-McConnell fits of static EXSY data shown in Figure S18 for 0.5 M LiTFSI, 1 M LiTFSI, and 0.5 M LiTFSI + 0.5 M LiNO3.…”
Section: Galvanostatic Cyclingmentioning
confidence: 99%